An introduction to mixed-signal IC test and measurement - Roberts, Gordon W., 1959- (Oxford series in electrical and computer engineering., 2012)
"With the proliferation of complex semiconductor devices containing digital, analog, mixed-signal and radio-frequency circuits, the economics of test has come to the forefront and today's engineer needs to be fluent in all four circuit types. Having access to a book that covers these topics will help the evolving test engineer immensely and will be an invaluable resource. In addition, the second edition includes lengthy discussion on RF circuits, high-speed I/Os and probabilistic reasoning. Appropriate for the junior/senior university level, this textbook includes hundreds of examples, exercises and problems"--Provided by publisher.